Senescence in Mesenchymal Stem Cells: Functional Alterations, Molecular Mechanisms, and Rejuvenation Strategies - Liu, Jing; Ding, Yue; Liu, Zhongmin; Liang, Xiaoting (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem cells (MSCs) are multipotent cells capable of self-renewal and differentiation, and mounting evidence has reported their therapeutic values in various clinical situations. However, as they age, MSCs gradually lose their self-renewal and regenerative potential, while the occurrence of cellular dysfunction strongly arises. On one hand, stem cell aging and exhaustion are considered as one of the hallmarks of organismal aging and functional attrition. On the other hand, MSCs do not proliferate infinitely, but undergo only a limited number of population doublings in a process termed senescence. Senescence greatly hampers the clinical application of MSC since it requires an extensive expansion to get substantial cell number for cell therapy. Here we review the current knowledge of the phenotypic and functional characteristics of senescent MSCs, as well as molecular mechanisms that involved in MSC aging and strategies to rejuvenate senescent MSCs. This may offer opportunities to prevent, postpone, or even reverse the kinetics with which MSCs aged.